PENGARUH MODEL CASE BASED LEARNING BERBANTUAN MEDIA YOUTUBE TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X MAN 1 KOTA PADANG - Koto, Juliana; Putri, Delsy Arma; Emidar; Indriyani, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Case Based Learning (CBL) model assisted by YouTube media on the negotiation text writing skills of class X students of MAN 1 Padang City. This study used a quantitative approach with a pre-experimental design in the form of a one-group pretest–posttest design. The research sample consisted of 33 students determined through a purposive sampling technique. The research instrument was a negotiation text writing performance test assessed based on aspects of structure, content, linguistic rules, and accuracy of spelling. Data were analyzed using a paired sample t-test to examine differences in abilities before and after treatment. The results showed that the average student writing skills increased from 49.48 in the pretest to 82.75 in the posttest, with a difference of 33.27. This increase indicates a significant difference in abilities between before and after the implementation of the learning model. These findings indicate that the integration of the CBL model with YouTube media has the potential to improve negotiation text writing skills, especially in the aspects of developing a logical text structure, content accuracy, and language use.